MENINGKATKAN PENGETAHUAN BACA TULIS AL-QUR’AN PADA ANAK TPA Al-MAGFIROH DENGAN METODE QUESIONER DI DESA SUMBER MAKMUR KECAMATAN BANDING AGUNG - Jepri Saputra; Mutia Mawardah (Bajang Institute, 2022)
In the prosperous source village, after several days of observing and interviewing the behavior of the children of the Al-Magfiroh Mosque TPA, the children still had difficulty understanding the lessons of reading and writing the Koran because the learning methods used were less efficient. Children tend to just memorize the lessons given and pay less attention to what is taught by the teacher which causes the child to have difficulty understanding and remembering what has been taught. The methods used in the scientific activities of the Thematic Real Work Lectures are as follows: Observations Observations were carried out on August 19, 2021 directly at Al-Magfiroh TPA 18:30 - 20:30 WIB. Interview The author conducted direct interviews with the Al-Magfiroh TPA teacher at the time of observation. Forming study groups This study group was created with the aim that the program runs well and does not cause crowds. Lecture The author plays a role in the process of the questionnaire learning method program where the author explains, guides, directs the program materials to be taught and creates a conducive atmosphere for children. Measuring Instruments The questionnaire method was given to the children and was carried out orally. The purpose of this activity is to increase the knowledge of reading and writing the Qur'an in Al-Magfiroh TPA children